Liquid Organic Hydrogen Carriers: Model Catalytic Studies on the Thermal Dehydrogenation of 1-Cyclohexylethanol on Pt(111) - Schwaab, Valentin; Hemauer, Felix; Freiberger, Eva Marie; Waleska-Wellnhofer, Natalie; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2023)
The molecule pair of 1-cyclohexylethanol and acetophenone represents an interesting system for a chemical hydrogen storage cycle as it combines two different classes of so-called liquid organic hydrogen carriers (LOHCs), namely hydrogenated, formerly aromatic cyclic hydrocarbons and alcohols, i.e., hydrogenated carbonyls. In particular, the latter have recently attracted much attention due to their favorable dehydrogenation temperatures and the possibility to convert them directly into electricity in specially designed direct-LOHC fuel cells. Herein, we investigate the temperature-triggered dehydrogenation reaction of 1-cyclohexylethanol to acetophenone on a Pt(111) model catalyst using synchrotron-based temperature-programed X-ray photoelectron spectroscopy. To obtain a complete picture of the reaction mechanism, we consider not only the individual surface reactions of 1-cyclohexylethanol and acetophenone but also those of two potential dehydrogenation intermediates, namely, the partially dehydrogenated 1-cyclohexylethanone and 1-phenylethanol. We find a stepwise dehydrogenation of 1-cyclohexylethanol: the first step around ∼210 K at the alcohol moiety yields the ketone 1-cyclohexylethanone. The second step above ∼260 K at the cyclohexyl group is accompanied by the loss of an H-atom at the molecule’s methyl group and leads to the formation of an acetophenone-like phenyl-C(O)-CH2 species at ∼340 K. The same species are also identified in the surface reactions of acetophenone, 1-phenylethanol, and 1-cyclohexylethanone in this temperature range. Overall, the system shows good thermal robustness: a complete dehydrogenation of the hydrogen-rich carrier occurs without damage to the carbon framework.
CRIS-Team Scopus Importer:2023-07-07